2018
DOI: 10.3758/s13428-018-1077-9
|View full text |Cite
|
Sign up to set email alerts
|

Word prevalence norms for 62,000 English lemmas

Abstract: We present word prevalence data for 61,858 English words. Word prevalence refers to the number of people who know the word. The measure was obtained on the basis of an online crowdsourcing study involving over 220,000 people. Word prevalence data are useful for gauging the difficulty of words and, as such, for matching stimulus materials in experimental conditions or selecting stimulus materials for vocabulary tests. Word prevalence also predicts word processing times, over and above the effects of word freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
209
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 170 publications
(221 citation statements)
references
References 46 publications
(42 reference statements)
2
209
0
Order By: Relevance
“…LDT latencies were standardized as z-scores (these minimize the influence of a participant's overall processing speed and variability; Faust, Balota, Spieler, & Ferraro, 1999), and all predictor variables were meancentered. The lexical variables letter length and letter length squared (length 2 ; New, Ferrand, Pallier, & Brysbaert, 2006), word frequency, word prevalence (Brysbaert, Mandera, McCormick, & Keuleers, 2018), and OLD were entered in Step 1, and the semantic variables were entered in Step 2. These semantic variables included age of acquisition, concreteness, BOI and, in light of the nonlinear BOI relationships depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…LDT latencies were standardized as z-scores (these minimize the influence of a participant's overall processing speed and variability; Faust, Balota, Spieler, & Ferraro, 1999), and all predictor variables were meancentered. The lexical variables letter length and letter length squared (length 2 ; New, Ferrand, Pallier, & Brysbaert, 2006), word frequency, word prevalence (Brysbaert, Mandera, McCormick, & Keuleers, 2018), and OLD were entered in Step 1, and the semantic variables were entered in Step 2. These semantic variables included age of acquisition, concreteness, BOI and, in light of the nonlinear BOI relationships depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our aim was to choose to-be-learned target words which would be unfamiliar to our participants at the start of the experiment. Forty-two rare English words (13 nouns, 17 adjectives, and 12 verbs) were selected from norms provided by Brysbaert, Mandera, McCormick, and Keuleers (2018) as being low prevalence words, where prevalence is derived from the percentage of people who know the word (M = À0.02; Range = À0.34 to 0.45) (see Keuleers, Stevens, Mandera, & Brysbaert, 2015). Negative prevalence values indicate that words are not known by the majority of people, making them ideal stimuli for word learning experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Thereby, words like "banana" are rated as relatively concrete while words like "idea" are rated as relatively abstract (Brysbaert et al, 2014). Empirical research has shown that relatively concrete words are more easily processed than abstract words in a variety of tasks, including word recognition (e.g., Strain, Patterson, & Seidenberg, 1995; but see Brysbaert, Mandera, McCormick, &Keuleers, 2018, andBrysbaert, Stevens, Mandera, &Keuleers, 2016, for contrasting findings), memory tasks (e.g., Jefferies, Frankish, & Lambon Ralph, 2006), comprehension tasks (e.g., Kounios & Holcomb, 1994), and production tasks (e.g., Wiemer-Hastings & Xu, 2005).…”
Section: Concreteness and Metaphoricitymentioning
confidence: 99%